Assessment of caprock integrity utilising rock failure prediction methodology for carbon capture and storage (CCS): A review - Nur Najwa Syuhada, Suhaidi; Foo, F. K.; Norasyikin, Ismail (Trans Tech Publications Inc., 2025)
This paper reviews the advancement in assessing caprock failure for Carbon Capture and Storage (CCS). Caprock plays a pivotal role in structural trapping as it acts as a seal to prevent carbon dioxide (CO2) leakage. However, when a substantial volume of CO2 is injected into the geological formation, the risk of shear failure associated with certain fractures and faults increases, potentially leading to CO2 escaping into the atmosphere. Such an outcome directly contradicts the fundamental purpose of CCS, which aims to securely contain CO2 and prevent its release into the atmosphere, thereby mitigating its impact on climate change. The review highlights Mohr-Coulomb criterion as rock failure prediction methodology to facilitate predict caprock behavior under pressure. This review has identified a gap in understanding the mechanism of structural trapping, particularly on caprock integrity for an effective CCS implementation.